2012
DOI: 10.1134/s1070428012050077
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical calculations of chemical shifts in NMR spectra of organic molecules: V. Stereochemical structure of unsaturated phosphonic acids dichlorides from 31P NMR spectral data

Abstract: The stereochemical structure of unsaturated phosphonic acids dichlorides containing fragments C=C-POCl 2 and C=N-POCl 2 was investigated by 31 Р NMR spectroscopy and quantum chemistry. Starting from the experimental measurement and theoretical calculation of 31 Р NMR chemical shifts confi gurations were assigned and the conformational composition of compounds under study was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In several systematic studies it was shown 48-55 that a satisfactory agreement between calculations and experiments is observed when quite a ''heavy'' basis set or high level of theory ‡ was used although deviations and exceptions were also found. In fact, there are relatively few reports on 31 P NMR CS calculations using quantum chemical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In several systematic studies it was shown 48-55 that a satisfactory agreement between calculations and experiments is observed when quite a ''heavy'' basis set or high level of theory ‡ was used although deviations and exceptions were also found. In fact, there are relatively few reports on 31 P NMR CS calculations using quantum chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are relatively few reports on 31 P NMR CS calculations using quantum chemical methods. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In several systematic studies it was shown [48][49][50][51][52][53][54][55] that a satisfactory agreement between calculations and experiments is observed when quite a ''heavy'' basis set or high level of theory ‡ was used although deviations and exceptions were also found. It is necessary to stress that all these studies were focused only on the restricted types of small size compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the reactions of trichloro(2 ethoxyethenyl) phosphonium and trichloro(styryl)phosphonium hexa chlorophosphorates with triethylamine were studied by 1 Н, 13 С, and 31 Р NMR spectroscopy. It was shown that the primary reaction products are phosphonyl chlorides.…”
Section: Methodsmentioning
confidence: 99%
“…In a continuation of the earlier publications by Chernyshev and coauthors, in the paper, the molecule of phosphine, PH 3 , was taken as a reference with a value of phosphorus shielding constant of 606.11 ppm, as evaluated by Lantto, et al at the CCSD(T)/cc‐pwCV5Z level without taking into account relativistic, rovibrational, and temperature corrections. This nonrelativistic GIAO‐CCSD(T)/cc‐pwCV5Z shielding constant was then corrected by evaluating relativistic contribution at the four‐component Dirac–Coulomb level to give 624.309 ppm and finally rovibrationally and temperature corrected to give the final value of 614.758 ppm.…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%